The Total Factor Productivity of Libyan Banks, 2004 – 2010 - Alrafadi, Khalad M. S; Kamaruddin, Badrul Hisham; Yusuf, Mazila Md (International Journal of Business, Economics and Management, 2015)
This paper provides a comparative analysis regarding the performance of 17 Libyan banks over the period 2004 up to 2010. According to the relevant literature, there are few studies that measure both technical efficiency and Malmquist productivity index approach using non – parametric approach (DEA) for the banking sector in Libya. For this study, the DEA technique was used to estimate technical, pure technical, and scale efficiency of sampled banks by using DEAP software. . The results showed that the specialized banks have exhibited higher mean technical efficiency relative to commercial and private banks. This paper concludes with some policy implications of the results. The results for total factor productivity (TFP) showed 11 of 17 Libyan banks decline because TFP levels of banks drawn by negative technical efficiency change (less than 1) or by negative technological change, or both of them are negative.